Answer:
x = 3/7
x = 0.43
Step-by-step explanation:
Make x the subject
x > ×7 > + 4 > -4 = 3
3 > + 4 > -4 > ÷ 7 = x
The answer is b. The Remainder<span> Theorem says that if a polynomial </span>f(x<span>) is divided by </span>x<span> – k, then </span>the remainder<span> is </span>f(k). k=3 in our case, so the remainder is simply f(3). Plug in x=3 into <span>f(x) = 7x4 + 12x3 + 6x2 - 5x + 16. f(x)=946. So the answer is b.</span>
Answer:
The answer is x = 8/5
Step-by-step explanation:
6 - 5x + 2 = 3x - 12 + 2x
4 - 5x = 5x - 12
4 = 10x - 12
16 = 10x
8/5 = x
4,875 in expanded form is 4,000 + 800 +70 + 5 = 4,875
Answer:
B. 1 and -2
Explanation:
First, add up the equations:
x-x+3y+y=4
4y=4
y=1
Now, plug y into any of the original equations above and solve for x:
-x+1=3
-x=2
x=-2
Therefore, the answer is B. 1 and -2